Water balance and salt losses in competitive football - Maughan, R. J.; Watson, P.; Evans, G. H.; Broad, N.; Shirreffs, S. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
Fluid balance and sweat electrolyte losses were measured in the players and substitutes engaged in an English Premier League Reserve competitive football match played at an ambient temperature of 6-8 °C (relative humidity 50-60%). Intake of water and/or sports drink and urine output were recorded, and sweat composition was estimated from absorbent swabs applied to 4 skin sites for the duration of the game. Body mass was recorded before and after the game. Data were obtained for 22 players (age 21 y, height 180 cm, mass 78 kg) and 9 substitutes (17 y, 181 cm, 72 kg). All were male. Two of the players were dismissed during the game, and none of the substitutes played any part in the game. Mean ± SD sweat loss of players amounted to 1.68± 0.40 L, and mean fluid intake was 0.84 ± 0.47 L (n = 20), with no difference between teams. Corresponding values for substitutes, none of whom played in the match, were 0.40 ± 0.24 L and 0.78 ± 0.46 L (n = 9). Prematch urine osmolality was 678 ± 344 mOsm/kg: 11 of the 31 players provided samples with an osmolality of more than 900 mOsm/kg. Sweat sodium concentration was 62 ± 13 mmol/L, and total sweat sodium loss during the game was 2.4 ± 0.8 g. These descriptive data show a large individual variability in hydration status, sweat losses, and drinking behaviors in a competitive football match played in a cool environment, highlighting the need for individualized assessment of hydration status to optimize fluid-replacement strategies.